Community Service through Impactful Internship: Enhancing Administrative Governance and Human Resource Development in State-Owned Enterprises - Anggressya Octaviana Nur Rahayu; Hafid Aditya Pradesa; Muhammad Taufiq (Trescode Green Organization, 2025)
This article presents a comprehensive community service implementation contextualized through an